Calculation of Pleural Fluid Estimation Using Ultrasonography - Adityo Wibowo; Mia Elhidsi; Agus Dwi Susanto (Indonesian Society of Respirology (ISR), 2022)
Pleural effusion is an abnormal accumulation of fluid in the pleural space due to an imbalance in increased pleural fluid production and decreased absorption. An ultrasound device can be used to guide the procedure to evacuate the pleural effusion fluid, increasing the procedure's accuracy and lowering the risk of complications. Several calculation methods can be used to calculate the volume of fluid in both an upright sitting position and a supine position. Ultrasound is nearly 100% more accurate than chest X-ray in detecting pleural fluid.